Parcs à sculptures en Valais : vers une critique de l’économie de projet - Benoît Antille (Revue de Géographie Alpine)
Over the past decade, the canton of Valais in the Swiss Alps has witnessed a true craze for site-specific sculptures or installations linked to the landscape. The predominant curatorial model has been the landscape sculpture park. The decision to choose the natural environment as the context for monumental sculptures or installations suggests that a certain idea of “land art” serves as a model for the projects developed in the Valais. This model is seen as a way to develop cultural content in response to the structural changes affecting the rural and mountainous regions. The École Cantonale d’Art du Valais undertook a research project to gain a better understanding of this phenomenon. The project’s conclusions are summarised here. The main goals of this research were to identify the conditions that explain the rising number of art projects in response to territorial issues and to propose a critical analysis based on case studies from the Valais. Three main conditions were identified: an urbanisation process at play in the countryside, the development of managerial cultural policies in line with the concepts of the creative economy and the development of an economy of project work in the art world. In short, the analysis of the case studies from the Valais suggests a link between this economy of project work and the creation and legitimisation of low-stakes cultural “products.”